Nanochemistry in Vaccine Delivery: Lipid Nanoparticles, Polymers, and Hybrid Systems - Chandipwisa, Courage; Shimilimo, Agness; Zenda, Tendai Pride; Banda, Harrison (Sciences of Pharmacy, 2026)
Conventional vaccines face challenges in antigen stability, delivery efficiency, and scalability, particularly in low- and middle-income countries. Nanochemistry offers innovative approaches through lipid nanoparticles, polymeric carriers, and hybrid systems. This review evaluates these platforms using criteria such as physicochemical properties, immunological outcomes, translational feasibility, and One Health relevance. A narrative literature review was conducted across major databases between 2015 and 2025. Studies were screened by title and abstract, excluded if not directly relevant to vaccine delivery, and weighted according to design, with clinical trials prioritized over in vitro or modeling studies. Reference lists of key papers were also examined to ensure comprehensive coverage. Lipid nanoparticles supported mRNA delivery in licensed COVID-19 vaccines, achieving strong immune responses but with variability across populations and reported adverse events including myocarditis and anaphylaxis. Polymeric nanoparticles such as PLGA and chitosan enabled controlled antigen release, though cost-effectiveness remains constrained by manufacturing and scalability challenges. Hybrid lipid-polymer systems demonstrated enhanced stability and multi-antigen presentation, with current evidence largely limited to preclinical studies. One Health implications are defined as the potential of nanochemistry to contribute to zoonotic disease prevention, food safety, and cross-species vaccine design, requiring clearer frameworks for integration. In conclusion, nanochemistry-based vaccine platforms show promise for advancing immunization strategies, but unresolved issues in safety evaluation, regulatory harmonization, and equitable access highlight the need for cautious interpretation and further interdisciplinary collaboration.